(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The advances ceramics have many applications such as aerospace, refectory, medical, electronic,…etc. In this work, the preparation of titanium carbide by using powder metallurgy technique from titanium and graphite has been investigated with different weight percentages are ((86:14),(83:17),(80:20) and (77:23)) wt.% titanium and graphite respectively. Titanium carbide was formed at (1200°C) for (8hr). The mechanical properties (microhardness, compression strength and wear rate) and characterization (SEM and XRD) of titanium carbide samples were studied. The results found that the best mechanical properties for titanium carbide samples prepared at (80:20) wt.% titanium and graphite respectively.